Targeted sequencing of refractory myeloma reveals a high incidence of mutations in CRBN and Ras pathway genes - Kortüm, Klaus Martin; Mai, Elias K.; Merz, Maximilian; Andrulis, Mindaugas; Jauch, Anna; Hillengaß, Jens; Goldschmidt, Hartmut; Raab, Marc-Steffen (Blood, 2016)
The incidence of mutations within the MAPK pathway, the CRBN pathway, and TP53 is significantly increased in drug-refractory MM. Mutations in CRBN might contribute to IMiD resistance in drug-refractory MM., In this study, targeted sequencing to screen 50 multidrug refractory multiple myeloma (rMM) patients was performed by using the Multiple Myeloma Mutation Panel. Patients were pretreated with both immunomodulatory drugs (IMiDs) and proteasome inhibitors (PIs), and 88%, 78%, and 68% were refractory to an IMiD, a PI, or both, respectively. The majority of patients had progressive (82%) or refractory (78%) disease immediately before sampling, with 43% being IMiD refractory and 46% being PI refractory in the most recent line of therapy. Compared with newly diagnosed MM, an increased prevalence of mutations in the Ras pathway genes KRAS, NRAS, and/or BRAF (72%), as well as TP53 (26%), CRBN (12%), and CRBN pathway genes (10%) was observed. Longitudinal analyses performed in 3 patients with CRBN mutations at time of IMiD resistance confirmed that these mutations were undetectable at earlier, IMiD-sensitive time points. Furthermore, the functional introduction of these mutations in MM cells conferred lenalidomide resistance in vitro. These data indicate a differential genetic landscape in rMM associated with drug response.